TECHNOLOGICAL WORK OF PROVIDING SECONDARY PROTECTION OF METAL STRUCTURES AGAINST CORROSION IN CONDITIONS OF CHEMICAL ACTIVE ENVIRONMENTS (Collection of scientific works «Modern structures of metal and wood», 2020)
The paper presents the results of  a  study aimed at  identifying signs corrosion damage,  conditions  for  monitoring  and  diagnosing  the  technical  condition  of  metal  structures according  to  the  level  corrosion  hazard.  The  paper  presents  the  results  of  a  study  aimed  at identifying  signs  corrosion  damage,  conditions  for  monitoring  and  diagnosing  the  technical  condition of metal structures according to the level corrosion hazard. Current state of constructions supporting tower the pipe, the operation which occurs in environments of chemical production Principles  process  approach  are  used  to  implement  the  tasks  of  managing  e  service  life  in corrosive  aggressive  environments.  The  study  identified  measures  to  ensure  durability  in accordance  with  the  level  of  corrosion  hazard  a  building  object,  identified  critical  indicators secondary protection of metal structures under the conditions corrosion impacts, within the interval estimates of the values considered indicators. The determination residual resource and the adoption decisions on the further operation facility is carried out in accordance with the established patterns changing  the  parameters  obtained  by  analyzing  mechanisms  damage  development  and  by determining the functional quality indicators. Assigned measures of secondary corrosion protection by the criterion corrosion hazard allow us to ensure reliability requirements and compliance with the regulatory provisions of the quality of metal structures based on the solution tasks r managing technological safety for a specified period. The list of tasks to be solved includes: identifying deviations from the requirements of current regulatory  documents  on  corrosion  protection;  assess  the  conformity  of  quality  indicators, constructive fitness and technological rationality means methods of corrosion protection to a given level  corrosion  hazard;  determine  the  requirements  for  the  selection  of  materials  and  protective systems  for  metal  structures  according  to  the  classification  features  regulatory  requirements;  to develop proposals for the use of tools and methods corrosion protection based on the examination of new materials and technologies for the assessment compliance with the requirements reliability and efficiency.